Gastric mucosal microbiota in a Mongolian population with gastric cancer and precursor conditions. Issue 8 (4th March 2020) - Gantuya, Boldbaatar; El Serag, Hashem B.; Matsumoto, Takashi; Ajami, Nadim J.; Uchida, Tomohisa; Oyuntsetseg, Khasag; Bolor, Dashdorj; Yamaoka, Yoshio
Summary: Background: Incidence and mortality of gastric cancer (GC) are high in Mongolia despite Helicobacter pylori in the Mongolian population being less virulent. Aim: To evaluate gastric bacterial microbiota profiles in patients with GC and its precursor histological conditions. Methods: We conducted a case‐control study among 48 GC and 120 noncancer patients (20 normal gastric mucosa [control], 20 gastritis, 40 with atrophy and 40 intestinal metaplasia [IM]). We performed 16S rRNA gene amplicon sequencing and compared taxonomic and functional prediction profiles based on the diagnosis group and H pylori infection status. Results: The highest overall bacterial alpha diversity metrics were observed in the control group, followed by the IM and cancer groups. The gastritis and atrophy groups had the least diversity. Lactobacilli and Enterococci were the dominant genus in several cancer patients especially in the absence of H pylori. In addition, Carnobacterium, Glutamicibacter, Paeniglutamicibacter, Fusobacterium and Parvimonas were associated with GC regardless of H pylori infection. Firmicutes were decreased in the gastritis and atrophy groups and increased in the IM and cancer groups. The functional metabolic activity of the Embden‐Meyerhof‐Parnas pathway and the utilization of sugar, were significantly increased in cancer group compared with the noncancer group. Conclusion: Microbial factors other than H pylori may play a role in Mongolian GC. We identified novel associations between GC and the genera Enterococcus, Lactobacillus, Carnobacterium, Glutamicibacter, Paeniglutamicibacter, Fusobacterium, and Parvimonas .